Tourist Growth and Adaptation of Local Community in Komodo National Park and Labuan Bajo, Manggarai Barat Regency, Indonesia - Imelda Masni Juniaty Sianipar; I Wayan Koko Suryawan (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
The surge in tourism within Komodo National Park and Labuan Bajo, located in the Manggarai Barat Regency of Indonesia, presents both opportunities and challenges for the local community and the environment. This study provides a comprehensive analysis of the significant increase in tourist arrivals and its implications on the ecological and social dynamics of the region. The allure of Komodo National Park's unique biodiversity and Labuan Bajo's picturesque landscapes has led to an unprecedented influx of tourists, emphasizing the critical need for sustainable tourism practices. This research examines the multifaceted impact of this growth on local communities, focusing on shifts in traditional livelihoods, the emergence of environmental pressures, and the strategies implemented to harmonize tourism development with ecological conservation. The study also explores various initiatives undertaken to mitigate the adverse effects of tourism, including community-based tourism projects and sustainable tourism policies. By offering a detailed assessment of these dynamics, the study provides valuable insights into effectively managing the challenges of tourism expansion in ecologically sensitive areas, ensuring the well-being of local communities, and preserving the region's natural heritage.